(untitled) (Western European Journal of Historical Events and Social Science, 2026)
This article examines how power and leadership are represented in William Golding’s “Lord of the Flies”. Special attention is given to Ralph’s elected leadership, Jack’s rise to command, the role of the conch, the use of speech, and the effect of fear on the group. The article analyzes selected scenes from the novel and reads those scenes together with existing criticism on authority, law, group dynamics, and political control. Close reading, textual analysis, and comparative use of scholarly sources are applied in order to reach clear results. The analysis shows that leadership in the novel is not presented as a natural gift only. Leadership is shown as something built through rules, consent, symbols, public speech, reward, and punishment. The study also shows that democratic authority becomes weak when shared belief in rules is lost, while violent leadership becomes stronger when fear and spectacle replace reason. Such results help explain why the island society moves from assembly to tribe, from discussion to command, and from moral order to chaos